Posfeminisme & cultural studies sebuah pengantar paling komprehensif Ann Brooks ; penerjemah, S. Kunto Adi Wibowo ; editor, Idi Subandi Ibrahim - BROOKS, Ann; Adi Wibowo, S. Kunto; Ibrahim, Idi Subandi (2004)
xvii, 357 hlm 21 cm